Specific Learning Disorder in School Age Children: A Literature Review on Early Detection and Its Challenges - Maya, Elyana Labib; Rachman, Amanda Azkiyah; Patandianan, Firdaus Kamma; Sari, Padmi Kartika; Elizar, Lale Justin Amelinda (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Specific Learning Disorder (SLD) is a neurodevelopmental disorder that affects a child’s basic abilities in reading, writing, and arithmetic. This disorder is often undetected in the early stages, leading to long-term academic difficulties and psychosocial problems. This literature review aims to provide a comprehensive overview of SLD, including its definition, classification, risk factors, signs and symptoms, diagnostic criteria, as well as the challenges and barriers in early detection. The methodology employed in this review was a structured literature search and critical appraisal of relevant sources, including peer-reviewed journal articles, academic textbooks, and established diagnostic guidelines. The results of the review indicate that early detection and appropriate intervention are crucial in helping children with SLD achieve optimal development. The roles of teachers, pediatricians, and other professionals are essential in the detection and management of SLD. Challenges in early detection include lack of awareness, limited resources, stigma, the standardization of diagnostic tools, as well as constraints in research and funding. Specific Learning Disorder (SLD) is a neurodevelopmental disorder that affects children’s academic abilities, particularly in reading, writing, and arithmetic. Early detection is crucial to enable timely intervention and prevent long-term consequences; however, various challenges still hinder early detection.